The Effect of the Game Based Learning Model Assisted by the Happy Reading Board (Harebo) on Students' Reading Interest - Rahmadita Prihandini, Putri; Malihatul Hawa, Anni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research is motivated by the lack of innovation in the application of reading models and media which causes a lack of interest in reading among students in learning in class IV of SD Negeri Langensari 04. The purpose of this study was to determine the defference and effect of the Game Based Learning (GBL) learning model assisted by the Happy Reading Board (HAREBO) on students' reading interest. The research method uses a quantitative approach with Collaborative and Competitive Multiplayer Games consisting of 2 classes, namely class IV students of SD Negeri Langensari 04. Data collection techniques with non-test techniques include pre-test and post-test questionnaires, observation, documentation, and interviews. The data analysis techniques used are the Independent Sample T-Test and Simple Linear Regression. The results of the study showed (1) There is a difference in the use of the GBL learning model assisted by the Happy Reading Board (HAREBO) on reading interest between the experimental class and the control class, as evidenced by the results of the Independent Sample T-Test showing a significance value of <0.001 <0.05. (2) There is an influence in the use of the GBL learning model assisted by the Happy Reading Board (HAREBO) on students' reading interest, with the results of the simple linear regression test showing a significance value of 0.001 <0.05. Based on the results of the study, it can be concluded that there is a significant difference between the experimental class and the control class, where the experimental class has an average of 80% while the control class has an average of 75%. These results indicate that the value obtained in the experimental class is higher than the control class. The use of the GBL learning model assisted by the Happy Reading Board (HAREBO) has an effect on students' reading interest by (R Square value 0.878 or 87.8%) the remaining 12.2% is influenced by other factors.